2011
DOI: 10.2528/pierc11022405
|View full text |Cite
|
Sign up to set email alerts
|

Planar W-Band Mixer With a Novel if-Block

Abstract: A planar W-band single balanced mixer is designed and measured in this paper. This mixer is realized by using two novel IFblock, a rat-race ring with the fifth port, two beamlead GaAs Schottky diodes and two RF chokes. The novel IF-block which designed the first time in W-band is employed to provide reflection points for IF signal and to provide low loss path in wide bandwidth for the RF and LO signals. To our knowledge, the mixer shows the best conversion loss at 95 GHz and the highest 1 dB power compression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
(14 reference statements)
0
7
0
Order By: Relevance
“…PIV measurements of the glottal flow using flexible and static models of the TVFs also demonstrated that the FVFs could interfere with the starting vortex and create vortices in this region [16,17]. Impingement of the glottal jet on the FVFs was also observed in the computational simulations when the Iaryngeal flow was assumed symmetric [26]. The rebound vortices in the current work detach the surface of the F'VFs and move in the Iaryngeal ventricle toward the TVFs; however, they do not reach the TVFs during the simulation.…”
Section: Comparison With Previous Investigation Of the Glottalmentioning
confidence: 75%
See 1 more Smart Citation
“…PIV measurements of the glottal flow using flexible and static models of the TVFs also demonstrated that the FVFs could interfere with the starting vortex and create vortices in this region [16,17]. Impingement of the glottal jet on the FVFs was also observed in the computational simulations when the Iaryngeal flow was assumed symmetric [26]. The rebound vortices in the current work detach the surface of the F'VFs and move in the Iaryngeal ventricle toward the TVFs; however, they do not reach the TVFs during the simulation.…”
Section: Comparison With Previous Investigation Of the Glottalmentioning
confidence: 75%
“…The growth of these instabilities forms vortical structures in the shear layer of the jet flow, and the impingement of these flow structures creates additional sources of sound [25]. Computational studies of Zhang et al [26] showed that the reattachment of the glottal jet flow with the FVFs created dipole acoustic sources. Medial compression of the FVFs in excised larynx experiments of Alipour et al [23] increased the sound intensity.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, these techniques cannot regenerate the urethral muscle tissue that regulates the exit of urine. With advances in materials science, innovative approaches based on regenerative medicine to regenerate damaged or weakened urethral tissues have been widely investigated using various biomaterials. Some research groups demonstrated that injection of cells (i.e., stem cells, progenitor cells, or adult cells) encapsulated with biomaterials at the defect promoted sphincter regeneration and restored the biological function in animal models and clinical applications. , In addition, sustained release of growth factors (GFs) from the bulking materials, such as basic fibroblast growth factor (bFGF) and nerve growth factor (NGF), has been implicated as a promising strategy to promote the regeneration of the urethral muscle and thus recover urethral muscle function. , However, for effective therapeutics, it is still a challenge to overcome the limitations of GF delivery in vivo, such as the very short half-life in vivo . Many researchers have endeavored to design biomaterials that allow for the long-term GF delivery and the retention of GF activity.…”
Section: Introductionmentioning
confidence: 99%
“…Millimeter-wave and submillimeter-wave frequency multipliers [1][2][3][4][5][6] and mixers [7][8][9][10][11][12][13][14] based on planar Schottky diodes are widely used for atmosphere and space detection. The multipliers are usually driven by an oscillator [15][16][17][18] or a phase-locked millimeter-wave source.…”
Section: Introductionmentioning
confidence: 99%